Testimony of place and time. Drawings by Fiszel Zylberg (Zber) from the internment camp in Beaune-la-Rolande (Loiret, France) - Piątkowska, Renata (Ars inspiratio: Studies dedicated to Professor Eleonora Jedlińska, 2024)
Fiszel Zylberberg (pseud. Zber) was born in Płock in 1909, studied at the Warsaw School of Fine Arts. He was a member of the graphic artists group “Black and White”. In 1936, he left for Paris. The outbreak of the Second World War interrupted Zber’s promising career (Zber was a name he used in Paris). Detained on 14 May 1941 during the so-called Jewish round-up, he was interned in the Beaune-la-Rolande camp. On 4 July 1942, he was taken to the Pithiviers camp, from where he was deported to Auschwitz on 17 July. There he died on 26 October 1942.This article centers on Zber’s wartime work: drawings done in the Beaune-la-Rolande camp. Portraits of fellow prisoners, camp’s views, pictures of prisoners’ daily life are an important historical source and personal document. By analyzing their content and materiality, we can see not only the camp’s everyday life, but also look deeper: into the hope of survival, into the dreams of the future. Collections of Zber’s campworks can be found at Cercil Musée-Mémorial des enfants du Vel d’Hiv in Orléans, at the Musée d’art et d’histoire du Judaïsme in Paris and at the United States Holocaust Memorial Museum in Washington DC.